التكنولوجيا المالية كبديل تمويلي مستحدث لإرساء الشمول المالي للمشروعات الصغيرة والمتوسطة - صخري, عبد الوهاب; بن علي, سمية (جامعة الوادي - University of Eloued, 2023)
هدفت هذه الدراسة لمعرفة مساهمة التكنولوجيا المالية على اعتبارها بديلا تمويليا مستحدثا في إرسائها الشمول المالي للمشروعات الصغيرة والمتوسطة، عن طريق تزويدها بالموارد المالية التي تحتاجها لتمويل استثماراتها في ظل عزوف البنوك التقليدية، تم استخدام المنهجين الوصفي والتحليلي تماشيا مع طبيعة الموضوع. هذا وتوصل الباحثان لمجموعة من النتائج والاستنتاجات أهمها أن التكنولوجيا المالية تلعب دورا فعالا في تعزيز الشمول المالي الرقمي لكافة شرائح المجتمع وتسهل عليهم الوصول الآمن والسريع للخدمات المالية والمصرفية، من جهة أخرى تعمل مختلف تقنياتها المبتكرة كالبيانات الضخمة والحوسبة السحابية إلى جانب منصات الائتمان الرقمية على تقليص الفجوة التمويلية للمشروعات الصغيرة والمتوسطة ومساعدتها على تجاوز القصور المالي الذي يكون عائقا رئيسيا أمام تقدمها وتوسعها. This Study aimed at identifying the contribution of Financial Technology as a novel financing alternative in establishing Financial Inclusion of Small and Medium-sized Enterprises, by providing them with Financial Resources they need to finance its investments under the reluctance of traditional Banks, The Descriptive and Analytical methodologies were used according with the nature of the topic. The Researchers reached to a set of results and conclusions, the most important of which is that Financial Technology plays an effective role in promoting Digital Financial Inclusion for all segments of society and facilitating safe and rapid access to Financial and Banking Services, On the other hand its various innovative technologies such as Big Data, Cloud Computing and Digital Credit Platforms are reducing the Financing Gap for Small and Medium-sized Enterprises and helping them overcome the financial deficit that’s a major impediment to their progress and expansion .
Financial Technology as a New Financing Alternative to the Establishment of Financial Inclusion for SMEs
مقال
Keywords: تكنولوجيا مالية؛ شمول مالي؛ مشروعات صغيرة ومتوسطة؛ خدمات مالية ومصرفية؛ فجوة تمويلية; Financial Technology; Financial Inclusion; Small and Medium-sized Enterprises; Financial and Banking Service; Financing Gap .